BNT162b2 vaccine induced variant-specific immunity, safety and risk of Omicron breakthrough infection in children aged 5 to 11 years: a cohort study - Yung, Chee Fu (2024)
There is little information on BNT162b2 vaccine-induced variant-specific immunogenicity, safety data and dynamics of breakthrough infections in pediatric populations. We addressed these questions using a prospective two dose BNT162b2 (10 mcg) vaccination cohort study of healthy children 5-11 years in Singapore. Follow up included blood samples at scheduled visits, daily vaccination symptom diary and confirmation of SARS-CoV-2 infection. Surrogate virus neutralization test (sVNT) and spike-specific T cell responses against SARS-CoV-2 variants were performed. The mean age of 127 participants was 8.27 years (SD 1.95) and 51.2% were males. The median sVNT level against original variant after 1 dose and 2 dose vaccination was 61.4% and 95.1% respectively (p < 0.0001). Neutralizing antibodies against the Omicron variant was the lowest, median 22.4% (IQR 16.5-30.8). However, T cell IFN-γ cytokine response against Omicron variant was high and remained so about 4 months after vaccination. Fever rate increased significantly from 4% (dose 1) to 11.5% (dose 2). The risk of Omicron breakthrough infection decreased by 7.8% for every 1% increase in sVNT inhibition level measured after dose 2 vaccination. BNT162b2 vaccines were safe, induced good T cell responses but poor neutralizing antibodies against Omicron in children. Low neutralizing antibody levels post-vaccination was predictive of subsequent breakthrough infection.